Extracellular Superoxide Dismutase (EC-SOD) Quenches Free Radicals and Attenuates Age-Related Cognitive Decline: Opportunities for Novel Drug Development in Aging - Levin, Edward D. (Current Alzheimer Research, 2005)
Superoxide dismutase (SOD) is one of the most effective mechanisms in physiology for inactivating reactive oxygen species. Elevated SOD activity can be therapeutically useful by protecting against oxidative stress-induced neurotoxicity. Acutely increased extracellular-SOD (EC-SOD) activity protects against neurobehavioral impairment caused by acute ischemia. Chronically increased EC-SOD activity may also be therapeutically useful by protecting against chronic oxidative stress-induced neurobehavioral damage that accumulates during the aging process. We have found that mice with genetic overexpression of EC-SOD do not show the aging-induced decline in learning and memory that control, wild type mice show. From 14-22 months of age, the EC-SOD overexpressing mice have significantly better spatial learning working memory function than that of controls. This effect is specific to the aging period. Young adult EC-SOD overexpressing mice do not have better learning and memory function than controls. The beneficial effects of increased EC-SOD activity with aging may be achieved without risk of impairment during younger ages by chronically administering EC-SOD mimetics from mature adulthood into the aging period. Novel EC-SOD mimetics may be useful in attenuating aging-induced cognitive impairments and other aspects of physiological decline with aging.
Keywords: neurodegeneration